Author Correction: Surface properties of SAR11 bacteria facilitate grazing avoidance. (December 2017) - Dadon-Pilosof, Ayelet; Conley, Keats; Jacobi, Yuval; Haber, Markus; Lombard, Fabien; Sutherland, Kelly; Steindler, Laura; Tikochinski, Yaron; Richter, Michael; Glöckner, Frank; Suzuki, Marcelino; West, Nyree; et al.
In the version of this Letter originally published, the authors incorrectly stated that primers 28F-519R were reported in ref. 54 to underestimate the abundance of SAR11 in the ocean. This statement has now been amended in all versions of the Letter.